Persepsi Siswa Terhadap Problematika dalam Pembelajaran Ips Kelas VIII SMP Negeri 1 Ngunut Tulungagung - Sendryna Mey Hidhayana; Jani Jani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Frequent emergence of problems faced by students in social studies learning activities problems experienced by students caused by many factors, both internal and external factors. Social studies learning at the junior secondary level is given or presented in an integrated manner to be more easily understood and learned by students. Because social studies is an integration of several branches of social sciences are simplified. The focus of research in writing this thesis is: (1) What are the problems of students in learning social studies class VIII SMP Negeri 1 Ngunut Tulungagung?, (2) What causes the emergence of problems experienced by students in learning social studies class VIII Smp Negeri 1 Ngunut Tulungagung?, (3)How can teachers overcome the problems experienced by students in social studies class VIII of Smp Negeri 1 Ngunut Tulungagung?. The objectives of the study are: (1) to describe the problems in social learning experienced by students of Grade VIII SMP Negeri 1 Ngunut Tulungagung, (2) to describe the causes of the emergence of problems in social learning experienced by students of Grade VIII SMP Negeri 1 Ngunut Tulungagung, (3) to describe how teachers overcome problems in social learning experienced by students of Grade VIII SMP Negeri 1 Ngunut Tulungagung. This research is categorized in qualitative research. with data collection techniques conducted by observation, interviews, and documentation with the research site at SMP Negeri 1 Ngunut Tulungagung. The subjects in this study were social studies teachers and eighth grade students of SMP Negeri 1 Ngunut Tulungagung. The results showed that: (1) problems experienced by grade VIII students in social studies, namely students who have minimal or less reading interest in social studies subjects. Availability of package books and worksheets for students is limited. The methods and learning media used by class teachers are less varied. The teacher is not in control of the class. (2) the cause of students experiencing problems in social science learning is that students do not have books and worksheets as companion books in social studies learning. Students are allowed to bring cellphones to school. The teacher's voice is less loud and clear when teaching. Many students are crowded during the class learning process. (3) how teachers overcome Student Problems in social studies learning is class management. Variety of learning (methods, media, and tasks). The teacher's attitude is firm. Outdoor learning.